Experimental investigation of the phase relations in the system Cu-Ni-S in the temperature range 1200 C to 700 C - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1996.